PENGARUH BUDAYA PERUSAHAAN PT. X TERHADAP KUALITAS PELAYANAN KEFARMASIAN YANG MEMILIKI DAMPAK KEPADA KEPUASAN DAN LOYALITAS PELANGGAN APOTEK UNIT BISNIS DEPOK PT. X - Sahat Saragi; Aritonang; Isti’anah Al-Fikriyah D (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
Companies that have interactions between customers and employees, especiallyemployees who are in frontline positions are very important in influencingcustomer satisfaction in purchasing activities made by each customer, corporateculture is one of the factors that can affect the performance of all employees,especially for employees in frontline positions . Pharmacy Depok Business UnitPT. X is a company that has interaction between customers and employees. Basedon survey data in 2019 regarding customer satisfaction owned by Apotek PT. XDepok Business Unit stated that it found a gap of around 0.24 from the expectedstandard. The purpose of this study is to determine the influence of the latest PT Xcorporate culture on the quality of pharmaceutical services that will result incustomer satisfaction and customer loyalty. Methodology, this study uses theChisquare method with a Crosstab approach with data collection carried out onthe quality of pharmaceutical services that will result in customer satisfaction andcustomer loyalty. The sample of this research is customers in 10 Pharmacies PTX Depok area. The results of the analysis were found. After the Crosstab of theCorporate Culture Variable on the Quality of Pharmaceutical Services Chisquare test showed a significance p-value of 0.456 (greater than 0.05), theCorporate Culture Variable on Customer Loyalty Chi-square test showed asignificance p-value of 0.129 (greater than 0.05), Pharmaceutical ServiceVariable on Customer Satisfaction Chi-square test shows a significant p-value of0.00 (less than 0.05), Pharmaceutical Service Variable on Customer Loyalty Chisquare test shows a significant p-value of 0.003 (smaller than 0.05), CustomerSatisfaction Variable on Customer Loyalty Chi-square test shows a significancep-value of 0.00 (less than 0.05). The conclusion, shows that there is a relationshipbetween Pharmaceutical Service and Customer Satisfaction, there is arelationship between Pharmaceutical Service and Customer Loyalty and there isa relationship between Customer Satisfaction and Customer Loyalty at ApotekDepok area PT. X.